Nikon D90 - Hilz, Corey (Focal digital camera guides., 2012)
Just bought a Nikon D60 and looking to combine practical know-how with inspiration? This one-stop, easy-to-read guide covers all the basic functions of the camera, and everything beyond. Inside, you'll find detailed explanations of every control and every feature, including full-color illustrations showing how changing each setting will affect your photographs But this book's greatest strength isn't its focus on the camera; it's the detailed, easy-to-follow instruction it offers on using your camera to take superior photographs. The lens, the subject matter, the light - all these variables are covered in depth, and always in the context of the Nikon D60. Written by a widely acclaimed photographer and photography instructor, the Nikon D60 Digital Camera Guide shows you how to get the shots you can see in your head but have never been able to capture with a camera. *Get up and running in five minutes with the quick start guide *Profit from dozens of tips and tricks *Master all of your camera's many features and controls *See first-hand how different settings affect your photos *Refine and manage your photos using the Nikon photo software *Be inspired by hundreds of gorgeous, full color photographs, and learn how to get the same effects in your own shots.